Rheological Properties of Very High-Strength Portland Cement Pastes: Influence of Very Effective Superplasticizers - Adriano Papo; Luciano Piani; Riccardo Ricceri (International Journal of Chemical Engineering)
The influence of the addition of very effective superplasticizers, that are commercially available, employed for maximising the solid loading of very high-strength Portland cement pastes, has been investigated. Cement pastes were prepared from deionized water and a commercially manufactured Portland cement (Ultracem 52.5 R). Cement and water were mixed with a vane stirrer according to ASTM Standard C305. The 0.38 to 0.44 water/cement ratio range was investigated. Three commercial superplasticizing agents produced by Ruredil S.p.a. were used. They are based on a melamine resin (Fluiment 33 M), on a modified lignosulphonate (Concretan 200 L), and on a modified polyacrylate (Ergomix 1000). Rheological tests were performed at 25°C by using the rate controlled coaxial cylinder viscometer Rotovisko-Haake 20, system M5-osc., measuring device MV2P with serrated surfaces. The tests were carried out under continuous flow conditions. The results of this study were compared with those obtained in a previous article for an ordinary Portland cement paste.